GEOLOGICAL INTERPRETATION OF NORTH MADURA OFFSHORE SEDIMENTARY BASIN BASED ON GRAVITY DATA ANALYSIS - Restu Ningsih; Imam Setiadi; Muh. Sarkowi; Akroma Hidayatika (Marine Geological Institute of Indonesia, 2023)
The area of north Madura offshore is one of the sedimentary basins within the North East Java Basin which has interesting paleogeographical developments. These developments are the result of various sedimentation processes and changes in the depositional environments. The purpose of this study is to identify subsurface geological structures, delineate sedimentary sub-basins, and estimate sediment thickness. For that, we do spectrum analysis, optimum upward continuation filtering, spectral decomposition analysis, 2D forward modeling and 3D inversion of gravity data. The results of the spectral analysis show that the average thickness of sedimentary rocks in the study area is around 3.788 km. From the gravity data analysis, 10 sedimentary sub-basins were delineated, indicating structural patterns of basement high, grabens, and faults. 2D and 3D modeling revealed four layers of stratigraphy, in order from youngest to oldest are Tertiary-Neogene sedimentary rocks with a density value of 2.1 gr/cc, the Tertiary-Neogene sedimentary rocks with a density of 2.3 gr/cc, the Tertiary - Paleogene sedimentary rocks with a density of 2.45 gr/cc, and the basement layer identified as volcanic igneous rock with a density of 2.67 gr/cc.